A história escolar e a teoria da atividade: relações e possibilidades formativas no ensinar e aprender - Cavalcante, Maria da Paz (2010)
This study investigates the manner in which the Activity Theory by Alexei Nikolaevich Leontiev contributed to the performance of a teacher who teaches History at the 8th year of elementary school, Escola Estadual Coronel Fernandes, in Luís Gomes - RN city. Her goal is to analyze the contributions of this theory in her teaching practice. It was opted by collaborative approach as formative strategy and was used as procedures for training of knowing the courses of study and thoughtful reflection sessions. It was used as techniques in the development of these cycles, the semistructured interview and the reflection sessions, the autoscopy and observation in real life. Regarding the theoretical foundation, held in these cycles, the teacher demonstrated to have appropriated some contributions from Activity Theory, besides relating them to her practice and understanding her importance to the improvement of teaching and learning of History. Concerning to the reflection sessions, the analysis showed that the participant has used of constructions of this theory and improved their practice, developing lessons of History so as to encourage student participation in oral and promote his integral development. The educational process, carried out on the practice of teacher, has shown an increase in her conscious learning that contributed to the improvement in their professional development. Before these findings, as needs for new thinking, this research recommends, especially the organization of teaching activities, based on this theory, which allows the teacher to improve the teaching and learning process contributing to student's full education